‘Kultura’ in the 21st Century Filipino Language: Revisiting the Western Critique of ‘Culture’ - Cabazares, Sheila Tampos; Cabazares, Janus (Philippine Social Sciences Review; PSSR Vol. 68 No. 2 2016, Ed. Rogelio Alicor L. Panao, 2017)
The critique of culture as a colonial objectification of the ‘other’ appears to remain oblivious that it is also a category shaped by forces other than Western discourses. This paper presents a view of culture articulated in 21st century Filipino language through contemporary academic and non-academic texts. Using linguistic analysis software to organize a combined total of 600 word occurrences of kultura into a corpus, we show how Filipinos use the term to denote ideas of unity and sharedness, especially in the non-academic context. Unlike the colonial use of the category to describe the subjugated ‘other,’ Filipinos use culture to refer to themselves as a collective, particularly in casual non academic discussions. Interestingly, in the academic context, the term is employed primarily as a lens or perspective through which social phenomena are viewed. In this domain, it is also used to talk about the ‘other.’ These nuances in academic, non-academic, Western, and non-Western discussions prove the category’s rich semantic content. Such richness is worth exploring further beyond Western hegemonic discourses and merits attention rather than renunciation.
Keywords: contemporary Filipino, corpus analysis, culture, kultura, Western hegemony